2019
DOI: 10.19045/bspab.2019.80117
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of NPK combination for seed production of onion (Allium cepa) crop

Abstract: Low productivity along with extensive usage of onion may cause shortage of this crop, as our country is facing high population problem. Mainly, there are two causes of low yield, lack of improved production technologies and poor quality of seed. Moreover, nutrient management is also an important aspect for getting higher yield. The current trial was conducted in RCBD with three replications and eight treatments. Treatments included different NPK fertilizer combinations i.e. T1: Control, T2: 30-20-00, T3: 60-40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
1
0
1
1
Order By: Relevance
“…Our data showed general negative relations between plant emergence and the concentration of most minerals in the different treatments of A. cepa, which differs from results previously found (Jilani et al 2019). The soil pH value of horizon A was not signi cantly correlated with emergence (Table 1).…”
Section: Discussioncontrasting
confidence: 99%
“…Our data showed general negative relations between plant emergence and the concentration of most minerals in the different treatments of A. cepa, which differs from results previously found (Jilani et al 2019). The soil pH value of horizon A was not signi cantly correlated with emergence (Table 1).…”
Section: Discussioncontrasting
confidence: 99%
“…Sulfur reported to improves the other major nutrient uptake of crops including garlic [14] As noted before, nitrogen is the major constituent of proteins and its abundant presence tends to increase the size of the leaves, which brings about an increase in carbohydrate synthesis [11]. The results of this study are in agreement with [44] and [32] who reported that the length and width of onion leaves increased with increased nitrogen rates. The results obtained in this experiment are generally in agreement with the findings of various Researchers where the application of NPS fertilizer alone or in combination increased the growth and development of garlic including the number, length and size of garlic leaves [5].…”
Section: Leaf Lengthsupporting
confidence: 91%
“…Иногда недостаточно убедительны. Однако не подлежат сомнению факт, что и азот, и фосфор активизируют физиологические процессы в тканях растительного организма, что безусловно, сказывается на вегетативных параметрах лука репчатого, которые можно оценить количественно [44,45,46,47,48]. Разница сведений связана с сортовыми различиями, почвенными и производственными условиями возделывания.…”
Section: роль азота и фосфора для протекания физиологических процессо...unclassified
“…Увеличенная толщина шейки является физиологическим нарушением, в основном зависящим от времени года, места возделывания лука и его сорта, а не от наличия минеральных питательных веществ в почве [16]. В отчете [44] указано, что азот в дозе 200 кг/га увеличивал число луковиц с толстой шейкой. Другие авторы [37] отметили, что внесение азота и фосфора не влияло на образование луковиц с толстой шейкой.…”
Section: влияние азота и фосфора на характеристики луковиц лука репча...unclassified